2018
DOI: 10.1111/rge.12177
|View full text |Cite
|
Sign up to set email alerts
|

Rb–Sr Dating of Gold‐Bearing Pyrite in the Jinchang Porphyry Cu–Au Deposit, Heilongjiang Province, NE China

Abstract: The Jinchang Cu-Au deposit in Heilongjiang Province, NE China, is located in the easternmost part of the Central Asian Orogenic Belt. Rb-Sr analyses of auriferous pyrite from the deposit yielded an isochron age of 113.7 AE2.5 Ma, consistent with previously reported Re-Os ages. Both sets of ages represent the timing of Cu-Au mineralization because (i) the pyrite was separated from quartz-sulfide veins of the mineralization stage in granite porphyry; (ii) fluid inclusions have relatively high Rb, Sr, and Os cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…With the development of analytical technology, numerous studies have shown that there are sufficient amounts of Rb and radiogenic Sr contents and variable Rb/Sr ratios in pyrite for Rb-Sr isotopic dating [46,47]. Therefore, pyrite Rb-Sr isotopic dating is widely used in determining the age of mineralization [48][49][50][51]. In this study, pyrite samples were first crushed to 40-60 mesh, and then fresh and highpurity particles were selected under binoculars.…”
Section: Pyrite Rb-sr Isotopic Datingmentioning
confidence: 99%
“…With the development of analytical technology, numerous studies have shown that there are sufficient amounts of Rb and radiogenic Sr contents and variable Rb/Sr ratios in pyrite for Rb-Sr isotopic dating [46,47]. Therefore, pyrite Rb-Sr isotopic dating is widely used in determining the age of mineralization [48][49][50][51]. In this study, pyrite samples were first crushed to 40-60 mesh, and then fresh and highpurity particles were selected under binoculars.…”
Section: Pyrite Rb-sr Isotopic Datingmentioning
confidence: 99%